Gifts and returns of senior officials of the regency of Algeria accompanying the trip of Dennoucheduring the period of the Deys 1671-1830 - belkacem, Hadda; bearcia, sabah (The Algerian Historical Journal, 2026)
Our study is a statistical study of the total value of the Dennouche that the Bey was providing to the regency’s treasury, and what was being allocated as gifts and returns to senior officials, as the latter was the most important category running the regency. This is done through addressing and defining Dennouche’s trip. The topic focused more on the nature of these gifts and returns, including money and in-kind assets. The most important conclusion we reached is that the Dennouche was one of the major sources of income for this category, so any delay in their submission or dissatisfaction with their value exposes the Bey to isolation and exile.